Environmental & architectural phenomenology. Vol. 9, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 1998)
Vol. 9, No. 2, Spring 1998 (includes “items of interest,” "citations received,” book reviews of James Steele's Architecture for People & Stewart Brand's How Buildings Learn, and essays by Paul Krapfel & Donald Snow).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals